Factors contributing to deep supercooling capability and cold survival in dwarf bamboo (Sasa senanensis) leaf blades - Ishikawa, Masaya; Oda, Asuka; Fukami, Reiko; Kuriyama, Akira (Frontiers in Plant Science, 2015)
Wintering Sasa senanensis, dwarf bamboo, has been known to employ deep supercooling as the mechanism of cold hardiness in its most of the tissues from leaves to rhizomes. The unique cold hardiness mechanism of this plant was further characterized using current year leaf blades. Cold hardiness levels increased from August (LT20: –11 °C) to December (LT20: –20 °C), which coincided with the initiation temperature of low temperature exotherms (LTE) detected in differential thermal analyses. When leaf blades were stored at –5 °C for 1-14 days, there was no nucleation of the supercooled tissue units compartmentalized by the longitudinal and transverse veins either in summer or winter. However, only summer leaves suffered significant injury after prolonged supercooling of the tissue units. This may be a novel type of low temperature-induced injury in supercooled state at subfreezing temperatures. When winter leaf blades were maintained at the threshold temperature (-20 °C), a longer storage period (1-7 days) increased lethal freezing of the supercooled tissue units. Within a wintering shoot, the second or third leaf blade from the top was most cold hardy and leaf blades at lower positions tended to suffer more injury due to lethal freezing of the supercooled units, which was not correlated with the leaf water content. LTE were shifted to higher temperatures (2-5 °C) after a lethal freeze-thaw cycle. The results demonstrate that the tissue unit compartmentalized with longitudinal and transverse veins serves as the unit of supercooling and temperature- and time-dependent freezing of the units is lethal both in laboratory freeze tests and in the field. To establish such supercooling in the unit, structural ice barriers such as development of sclerenchyma and biochemical mechanisms to increase the stability of supercooling are considered important. We discussed these mechanisms in regard to ecological and physiological significance in winter survival.